Gastroschisis: Initial Management according to General Practitioner Competence - Tri M. Ibrahim; Harsali Lampus; Jeiny Thomas (Universitas Sam Ratulangi, 2022)
Abstract: Gastroschisis is the most common congenital defect in the abdominal wall in the last 30 years.Â This may be related to increased incidence of prematurity and increased survival rate of premature babies. Defects in the abdominal wall usually occur less than 4 cm, located at the junction of umbilicus and normal skin.Relatively young maternal age (<21 years), as well as habits of consuming alcohol and drugs can increase the risk of gastroschisis.Diagnosis can be confirmed at prenatal stage by using USG, and at postnatal stage. Initial treatment consists of fluid resuscitation, oxygenation, decompressed nasograstic tube (NGT), and hypothermia prevention. In conclusion, gastroschisis needs immediate treatment by prevention of hypothermia in infants, administration of fluid and oxygen, and closure of defect. The overall survival rate is quite good and the prognosis depends on the condition of the gut at birth. Keywords: gastroschisisÂ Abstrak: Gastroschisis merupakan defek kongenital pada dinding abdomen yang paling umum ditemukan dalam 30 tahun terakhir. Hal ini mungkin terkait dengan peningkatan kejadian prema-turitas dan peningkatan kelangsungan hidup bayi prematur.Defek pada dinding abdomen terjadi biasanya kurang dari 4 cm dan terletak di antara sambungan umbilikus dan kulit normal. Usia ibu yang relatif muda (<21 tahun), kebiasaan mengonsumsi alkohol serta obat-obatan dapat mening-katkan risiko terjadinya gastroschisis. Diagnosis dapat ditegakkan saat prenatal dengan USG, dan postnatal. Penatalaksanaan awal meliputi resusitasi cairan, pemberian oksigenasi, pemasangan nasogastric tube (NGT) dekompresi, serta mencegah terjadinya hipotemia. Simpulan tulisan ini ialah gastroschisis memerlukan penanganan segera dengan melakukan pencegahan terjadinya hipotermia pada bayi, pemberian cairan, pemberian oksigenasi, dan penutupan defek. Tingkat kelangsungan hidup secara keseluruhan cukup baik dan prognosis tergantung pada kondisi usus saat lahir.Kata kunci: gastroschisis